2006
DOI: 10.1109/iecon.2006.348106
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed LQRI / PI based Control for Three-Phase UPQCs

Abstract: A mixed Linear Quadratic Regulator with an Integral action control technique applied to a Unified Power Quality Conditioner (UPQC) is presented. The proposed control approach becomes a robust strategy that is able to keep regulation and stability even under extreme parameters and load power factor variations. The design of the controller parameters uses the well known Riccati equation based on the discrete approximation of the linear model of the UPQC. Key waveforms based on simulated extensive work shows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Furthermore, the output feedback periodicalswitched controller is designed to stabilize the closed-loop system. The authors in [52], [74], [104], and [154] discuss the UPQC system modeling in detail.…”
Section: Upqc-state Of the Artmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the output feedback periodicalswitched controller is designed to stabilize the closed-loop system. The authors in [52], [74], [104], and [154] discuss the UPQC system modeling in detail.…”
Section: Upqc-state Of the Artmentioning
confidence: 99%
“…The three-phase system in abc frame is transferred into synchronous dqo frame. The system is then represented in state-space formulation [12], [22], [52], [74], [106], [151]. It is observed that the system is nonlinear on its states as well as on its outputs [73].…”
Section: Upqc-state Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…s  represents the series APF voltage, reference load voltage and source voltage. The system modeling aspects of the UPQC are reported in [56][57][58][59][60][61][62][63]. In [64], a mathematical modeling and design of a versatile UPQC are discussed clearly.…”
Section: Introductionmentioning
confidence: 99%